Keragaan Varietas dan Galur Padi Tipe Baru Indonesia dalam Sistem Ratun - Susilawati, ,; Purwoko, Bambang Sapta; Aswidinnoor, Hajrial; Santosa, Edi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
Eighteen Indonesian new plant type (NPT) of rice varieties and lines were evaluated in a ratoon system. The results showed that ratooning ability was related to the vegetative growth prior to harvest, which gave high ability ratoon growth. New plant type varieties and several lines of rice had better vegetative growth and produced higher ratoon than other genotypes. Ratoons started to develop 2-7 days after harvest, with an average number of leaf 2-4 per tiller. Number of productive tillers of ratoon ranged from 6.0 to 30.0 per hill, with number of grain per panicle ranged from 38.0 to 228.2, and grain weight per hill of ratoon 10.4 to 31.2 g, dependent on genotypes. Maturity of ratoon was also dependent on genotypes. On average, maturity was 68 days after harvest of the main crop. Grouping of ratooning ability based on hierarchical cluster analysis resulted in three groups, namely nine genotypes had high potential, fi ve genotypes had medium potential, and four genotypes had low potential. This study indicated that ratoon is potential to increase rice planting index in Indonesia. The genotypes with high ratoon ability need to be evaluated for agronomic performance in the fi eld. Keywords: new plant type, ratooning ability, rice